2018
DOI: 10.3389/fimmu.2018.02966
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Inflammatory Changes in Human Myometrial Cells by Cell Penetrating Peptide and Small Molecule Inhibitors of NFκB

Abstract: Complications arising from Preterm Birth are the leading causes of neonatal death globally. Current therapeutic strategies to prevent Preterm Birth are yet to demonstrate success in terms of reducing this neonatal disease burden. Upregulation of intracellular inflammatory pathways in uterine cells, including those involving nuclear factor kappa-B (NFκB), have been causally linked to both human term and preterm labor, but the barrier presented by the cell membrane presents an obstacle to interventions aimed at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 56 publications
(65 reference statements)
0
8
0
Order By: Relevance
“…5 A), or in the proportions of CD206 − and CD206 + macrophages in colonic biopsies from patients with IBD. Other investigators have reported increased proportions of less-mature monocyte-derived cells in inflamed samples from patients with IBD 17 . The difference between our data and other reports is unlikely to reflect differences in our patient population, as all samples designated as ‘active’ (CDa and UCa) were obtained from visibly-inflamed regions of the colon.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…5 A), or in the proportions of CD206 − and CD206 + macrophages in colonic biopsies from patients with IBD. Other investigators have reported increased proportions of less-mature monocyte-derived cells in inflamed samples from patients with IBD 17 . The difference between our data and other reports is unlikely to reflect differences in our patient population, as all samples designated as ‘active’ (CDa and UCa) were obtained from visibly-inflamed regions of the colon.…”
Section: Discussionmentioning
confidence: 87%
“…Much progress has already been made in identifying DC populations in the human intestine 12 17 , therefore, we focused on intestinal macrophage populations. Recent detailed descriptions of murine MNP populations have enabled clearer identification of these cells in samples from human tissue, including skin 18 , liver, lung, blood 19 and lymph nodes 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Cell-penetrating peptides (CPPs) induce cellular uptake in a receptor-independent manner. Since their discovery in the 90s [ 24 , 25 ] they have been employed to mediate uptake of oligonucleotides [ 26 ], peptides [ 27 ], antibodies [ 28 , 29 ] and nanoparticles [ 30 , 31 ]. Therefore, CPPs are also good candidates to enhance cellular uptake and tissue retention of tumor targeting agents.…”
Section: Introductionmentioning
confidence: 99%
“…NF-kB is a pleiotropic transcription factor that increases proinflammatory cytokine production, and regulation of its activation is therefore considered one of the approaches to reduce the risk of PTB [ 33 , 34 , 35 ]. Novel therapeutics that reduce inflammation by inhibiting NF-kB using anti-inflammatory drugs [ 36 , 37 , 38 ], cell-penetrating peptides, small molecule inhibitors [ 33 , 39 , 40 ], nonspecific inhibitors [ 41 , 42 , 43 , 44 ], and flavonoids are now being tested [ 45 , 46 ]. However, very few have made it to clinical trials so far and none are in use clinically, likely due to several issues including, but not limited to, the mode of delivery, placental permeability, teratogenicity, and transgenerational effects.…”
Section: Discussionmentioning
confidence: 99%